2018
DOI: 10.1177/1747021817740275
|View full text |Cite
|
Sign up to set email alerts
|

Faces, people and the brain: The 45th Sir Frederic Bartlett Lecture

Abstract: The fact that the face is a source of diverse social signals allows us to use face and person perception as a model system for asking important psychological questions about how our brains are organised. A key issue concerns whether we rely primarily on some form of generic representation of the common physical source of these social signals (the face) to interpret them, or instead create multiple representations by assigning different aspects of the task to different specialist components. Variants of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 233 publications
1
59
0
Order By: Relevance
“…Especially, their endorsement of the importance of the laboratory to world synergy, in which practical questions act as strong tests of theory, and theories are in turn refined to cope with practical questions. We agree too that understanding the nature of laboratory and real-world tasks is crucial, as it is in almost any area of face perception research (Young, 2018). We agree too that understanding the nature of laboratory and real-world tasks is crucial, as it is in almost any area of face perception research (Young, 2018).…”
Section: Commentarymentioning
confidence: 90%
See 1 more Smart Citation
“…Especially, their endorsement of the importance of the laboratory to world synergy, in which practical questions act as strong tests of theory, and theories are in turn refined to cope with practical questions. We agree too that understanding the nature of laboratory and real-world tasks is crucial, as it is in almost any area of face perception research (Young, 2018). We agree too that understanding the nature of laboratory and real-world tasks is crucial, as it is in almost any area of face perception research (Young, 2018).…”
Section: Commentarymentioning
confidence: 90%
“…This approach belongs in a time-honoured tradition (Baddeley, 2018) that has been fundamental to much work on face recognition (Davies & Young, 2017). We agree too that understanding the nature of laboratory and real-world tasks is crucial, as it is in almost any area of face perception research (Young, 2018).…”
Section: Commentarymentioning
confidence: 93%
“…A strength of the present research is the complementary use of ambient and averaged face‐like images to show that multiple interacting cues may contribute to partner preferences. In studies 2 and 4, ambient stimuli allowed these cues to vary naturally, facilitating the identification of the main traits involved in partner preferences, which is a theoretically powerful approach (Sutherland et al ., ; Vernon et al ., ; Young, ). In study 3, averaged images were used to emphasize the characteristics common to a specific factor.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient face images represent a novel approach to examining first impressions of potential partners. Because ambient images maintain the highly variable properties that are present in natural environments, they can allow findings to be more directly generalized to real‐life contexts, relative to controlled stimuli (Sutherland, Rhodes, & Young, ; Young, ).…”
Section: Studymentioning
confidence: 99%
“…However, changes in viewpoint make the process of face recognition more difficult, because so many different views can be generated from the same identity. Despite this challenge, we can recognize familiar faces from different viewpoints with relative ease (Hancock et al, 2000), raising the critical theoretical question of how this viewpoint-invariance for recognizing famil-iar faces is achieved (Young and Burton, 2017;Young, 2018). Cognitive models of face processing have suggested that the recognition of facial identity is based on a view-invariant representation that receives convergent input from relatively viewpoint-specific representations (Bruce and Young, 1986; but see Tarr and Bulthoff, 1998;Burton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%